Subacute Combined Degeneration, Pernicious Anemia and Gastric Neuroendocrine Tumor Occured Simultaneously Caused by Autoimmune Gastritis - Zhang, Nan; Li, Rui-Hua; Ma, Lin; Li, Na; Shan, Pei-Yan; Wang, Xing-Bang; Liu, Ai-Fen (Frontiers in Neuroscience, 2019)
Subacute combined degeneration (SCD) is a relatively rare myelopathy mainly caused by vitamin B12 deficiency. There are many causes contributing to vitamin B12 deficiency. Autoimmune gastritis might lead to severe vitamin B12 malabsorption and in its advanced stage pernicious anemia (PA) may occur. Besides, long-term hypergastrinemia arising from achlorhydria in autoimmune gastritis is associated with neuroendocrine tumors (NETs). Patients diagnosed with SCD coexistent with PA and NET are seldomly reported. We describe a 34-year-old woman with an initial complaint of progressively fatigue, weakness and numbness in her limbs and disturbed gait. Physical examination revealed appearance of anemia, ataxia, decrease of superficial and deep sense and positive Babinski’s sign. Laboratory tests disclosed macrocytic anemia, elevated intrinsic factor antibody and spinal MRI showed extensive T2-weighted hyperintensity in the dorsal columns. A gastric polyp was found by gastroscopy and histology showed an NET in the background of severe atrophic gastritis. Symptoms of the patient were relieved by a multidisciplinary therapy. In patients with SCD, PA should be suspected and prompt further investigations to elucidate causes and direct treatment.